DESIGN OF ELASTIC SKIN AND HONEYCOMB SANDWICH CONNECTION SCHEME FOR COMPOSITE FLEXIBLE SKIN (MT) - GUO YuChao; AI Sen; YIN WeiLong; WANG LiKai; NIE XiaoHua (Jixie qiangdu)
In order to solve the problem of low connection strength between elastic skin and honeycomb sandwich of composite flexible skin for variant aircraft, a “two-step bonding” connection scheme is proposed. Firstly, the polyurethane fiber cloth and honeycomb are bonded by epoxy resin structural adhesive, then the silicone rubber sheet and the spandex fiber cloth are bonded by the silicone rubber adhesive, and the manufacturing method is given. Finally, “two-step bonding” experimental piece and “direct bonding” experimental piece were prepared respectively, and the bonding strength experiment and comparative analysis were carried out, The results show that the bonding strength of the “two-step bonding” experimental piece is five times that of the “direct bonding” experimental piece.